2004
DOI: 10.1515/come.2004.1.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Journalists and jabs: Media coverage of the MMR vaccine

Abstract: The MMR vaccine became front-page news in early February 2002, in a much reported controversy about alleged links between MMR and autism. We examine both media content and public opinion and knowledge to explore how this controversy was presented, and, in turn, how this coverage influenced public perceptions. The news coverage of MMR was monitored over a seven and a half month period from 28 January to 15 September, 2002. Two national surveys were conducted-in April and in October, 2002-both based on over 1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 20 publications
0
48
1
1
Order By: Relevance
“…However, this result was inconsistent with other studies which consider internet as the main source of information on vaccination. 18,29 The question 18 in the practice questionnaire assessed and evaluated the respondents' previous practices in immunizing their elder children. The result showed that 96% of mothers had vaccinated their elder children in the same pattern as of their present child.…”
Section: Discussionmentioning
confidence: 99%
“…However, this result was inconsistent with other studies which consider internet as the main source of information on vaccination. 18,29 The question 18 in the practice questionnaire assessed and evaluated the respondents' previous practices in immunizing their elder children. The result showed that 96% of mothers had vaccinated their elder children in the same pattern as of their present child.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies about autism covered in the print media focused on diagnosis, intervention, symptom, therapy, cause (Clarke 2008;Sigman 2007;Speers and Lewis 2004;Spittler 2009;Wallis and Park 2006), legal case, education, personal story, and personality (Douwe 2009;Riggott 2005), and government policy (Kitzinger 2000). Clarke (2011) recently analyzed magazine coverage of autism and found that magazines for general audience emphasized research findings whereas the magazines for women stressed tragedy or hopes.…”
Section: Issue Framingmentioning
confidence: 99%
“…The article received considerable coverage in the media and spawned a highly publicized debate between scientists, who uniformly found no empirical evidence for the MMR-autism link (see, for example, Offit and Coffin 2003), and advocates and parents, who cited anecdotal evidence for the relationship. 1 Subsequent to the publication of the study and the media attention it received, MMR vaccination rates declined in some areas of the United Kingdom (Jefferson 2000;O'Dell and Brownlow 2005;Serpell and Green 2006;Speers and Lewis 2004). In Dublin, Ireland, the decrease in MMR vaccination led to an outbreak of measles that resulted in the hospitalization of over 100 children and the death of three children (McBrien et al 2003).…”
Section: History Of the Mmr Controversymentioning
confidence: 99%
“…Many scientists consider media coverage of the Wakefield study to have been a driving influence in parents' decisions not to immunize their children with MMR (Speers and Lewis 2004). On the other hand, some scholars have highlighted changes that they feel need to be made in the practice of both science and journalism in order to promote better public understanding of the science of vaccines and autism and to prevent such public health crises in the future.…”
Section: History Of the Mmr Controversymentioning
confidence: 99%